Hardness Studies on Solution Grown Lithium Potassium Sulphate Single Crystals – An Inorganic Nonlinear Optical Material - Murugadoss, K; Pasupathi, G (International Journal of Chemistry and Materials Research, 2015)
Single crystal of Lithium Potassium sulphate is grown by slow evaporation technique at room temperature. The grown crystal is characterized by Vickers micro hardness test. It is carried out by over a load with a range of 10 – 100 gm on the selected smooth plane surface of the crystal. Vickers’s hardness values (Hv) are calculated for selected applied load and it is found to be increasing with the increasing applied load. The Meyer’s index number (n) is .calculated from the Vickers hardness number and it confirms that the grown material belongs to soft material category. The Elastic stiffness constant (C11) is calculated using Wooster’s empirical relation. Further the Yield strength (σv), Brittleness index (B), and the Fracture toughness (Kc) are calculated to the grown LKS crystals.